2019
DOI: 10.3390/ijms20081897
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Model for Predicting Drug-Induced Hepatotoxicity

Abstract: As one of the leading causes of drug failure in clinical trials, drug-induced liver injury (DILI) seriously impeded the development of new drugs. Assessing the DILI risk of drug candidates in advance has been considered as an effective strategy to decrease the rate of attrition in drug discovery. Recently, there have been continuous attempts in the prediction of DILI. However, it indeed remains a huge challenge to predict DILI successfully. There is an urgent need to develop a quantitative structure–activity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 62 publications
2
94
0
Order By: Relevance
“…Predicting liver toxicity from chemical structure has been a preoccupation of over two decades, first starting somewhat timidly with local models [44,45], to move later also to global models [46,47]. Many of the previous models used relatively small size datasets (less than 400 compounds) [48,49]; studies based on datasets larger than DILIrank have also been published [11,17,[50][51][52], but the authors of DILIrank used a methodology that, in theory at least, was superior and more consistent with the totality of available clinical data. The total DILIrank dataset includes 1036 compounds, but 254 were classified as of "ambiguous DILI-concern", because the causality evidence was limited; besides, it took great care in defining DILI negatives, which varied among four large sources previously studied, labeling some compounds previously considered of no DILI concern as of less DILI concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predicting liver toxicity from chemical structure has been a preoccupation of over two decades, first starting somewhat timidly with local models [44,45], to move later also to global models [46,47]. Many of the previous models used relatively small size datasets (less than 400 compounds) [48,49]; studies based on datasets larger than DILIrank have also been published [11,17,[50][51][52], but the authors of DILIrank used a methodology that, in theory at least, was superior and more consistent with the totality of available clinical data. The total DILIrank dataset includes 1036 compounds, but 254 were classified as of "ambiguous DILI-concern", because the causality evidence was limited; besides, it took great care in defining DILI negatives, which varied among four large sources previously studied, labeling some compounds previously considered of no DILI concern as of less DILI concern.…”
Section: Discussionmentioning
confidence: 99%
“…A review found, in 2014, that in models published up to that time point, the external validation datasets had been "quite small" (20-50 drugs), and that for the larger external datasets the model performance seemed to be "less favorable" [53]. One of the best-performing ensemble models recently published used three external validation datasets and had a pooled balanced accuracy of 71.60% [17]. Although based on a different dataset (DILIrank), our model compares favourably, with a balanced accuracy in the nested cross-validation (i.e., an average of 10 external datasets) that is slightly superior for several meta-models attempted and higher than 74% (as shown in the results section).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major challenges associated with the prediction of DILI using in vitro approaches lie in identifying relevant assays (5) and extrapolating from assay concentrations to in vivo blood concentrations associated with a hepatotoxic risk (6). Numerous in silico models have been generated based on molecular structure (7)(8)(9)(10)(11)(12) and in vitro readouts, such as bioactivity (13) and gene expression (14) in cell culture, which are able to predict DILI better than random, but with a…”
Section: Introductionmentioning
confidence: 99%
“…In the case of computational predictions, DILI is often simplified to a classification problem, i.e. separating compounds with or without this annotation in a data set (7)(8)(9)11,13). These labels, however, do not provide information on important factors such as dose-dependency or affected patient population, and consequently the practical applicability of such models is limited.…”
Section: Introductionmentioning
confidence: 99%